2015
DOI: 10.3390/ma8041831
|View full text |Cite
|
Sign up to set email alerts
|

The Microstructural Evolution and Mechanical Properties of Zr-Based Metallic Glass under Different Strain Rate Compressions

Abstract: In this study, the high strain rate deformation behavior and the microstructure evolution of Zr-Cu-Al-Ni metallic glasses under various strain rates were investigated. The influence of strain and strain rate on the mechanical properties and fracture behavior, as well as microstructural properties was also investigated. Before mechanical testing, the structure and thermal stability of the Zr-Cu-Al-Ni metallic glasses were studied with X-ray diffraction (XRD) and differential scanning calorimeter. The mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Although metallic glasses (MGs) have received much attention since its discovery in 1960s due to their outstanding mechanical properties such as ultrahigh strength, superior elasticity, and excellent thermo-plasticity, some weaknesses limit their industrial applications, including the difficulty to obtain normal size and brittleness at room temperatures [ 1 , 2 , 3 , 4 ]. The latter weakness makes MGs impossible to be used as structural materials.…”
Section: Introductionmentioning
confidence: 99%
“…Although metallic glasses (MGs) have received much attention since its discovery in 1960s due to their outstanding mechanical properties such as ultrahigh strength, superior elasticity, and excellent thermo-plasticity, some weaknesses limit their industrial applications, including the difficulty to obtain normal size and brittleness at room temperatures [ 1 , 2 , 3 , 4 ]. The latter weakness makes MGs impossible to be used as structural materials.…”
Section: Introductionmentioning
confidence: 99%
“…The shear band plays a decisive role in controlling the deformation of metallic glasses (MGs) at room temperature, in which large plastic strain is concentrated [1,2,3]. A shear-band process includes formation, propagation, and arrest [4].…”
Section: Introductionmentioning
confidence: 99%
“…These include observations under abrasion corrected transmission electron microscopy [31], synchrotron light [32] [33] [34] [35] and in-situ studies [36] [37] [38] [39] but none have been made on the detailed use of more recent and advanced electron back scattered diffraction. Only three notable studies have been recently reported [40] [41] [42] but they are only qualitative and are limited by mere generalised phase identification. This is a new and unique technique which has been reported as complimentary to transmission electron microscopy [43] [44].…”
Section: Introductionmentioning
confidence: 99%